Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work and Social Computing 2017
DOI: 10.1145/2998181.2998356
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Collaborative Writing in the Classroom

Abstract: Group activities that use Google Docs for simultaneous collaborative writing and editing are increasingly common in higher education. Although studies show that synchronous collaboration can bring multiple benefits, such as enhanced productivity and writing quality, little is known about these writing practices in classrooms and their impact on students' writing. Using a mixed method approach, we conducted an empirical study that explores the different styles of synchronous collaboration in 45 Google Docs docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 26 publications
(15 reference statements)
4
22
1
Order By: Relevance
“…Some studies found a positive effect for CBCW on writing quantity (e.g., Daskalogiannaki, 2012;Doult & Walker, 2014;Mak & Coniam, 2008;Mills & Exley, 2014;Myers, 2014;Storch, 2011;Yim, Wang, Olson, Vu, & Warschauer, 2017) and quality (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;. Therefore, the researcher decided to investigate the effect of CBCW on both the quantity and quality of EFL students' writing.…”
Section: Cbcw and Writing Quantity And Qualitymentioning
confidence: 99%
“…Some studies found a positive effect for CBCW on writing quantity (e.g., Daskalogiannaki, 2012;Doult & Walker, 2014;Mak & Coniam, 2008;Mills & Exley, 2014;Myers, 2014;Storch, 2011;Yim, Wang, Olson, Vu, & Warschauer, 2017) and quality (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;. Therefore, the researcher decided to investigate the effect of CBCW on both the quantity and quality of EFL students' writing.…”
Section: Cbcw and Writing Quantity And Qualitymentioning
confidence: 99%
“…While group interactions may lead to higher quality group work, it may be the case that group outcomes are more important with regard to learning. Some authors have warned against a final product focus when looking at collaboration, as content-mastery is often the goal of much group work, not the final product the group creates (Yim et al, 2017). It has been shown empirically that successful group work leads to more retention of contents (Barron, 2003).…”
Section: The Effect Of Note-taking Quality On Learningmentioning
confidence: 99%
“…Similar to SCAPES, DocuViz uses the editing information gleaned from the revision histories and tracking changes on Google Docs, but provides additional information on the feedback source (peer vs. self-edit) and produces a visualization chart across different time points, indicating the authors, their portions of writing, and the time of editing (Wang, Olson, Zhang, Nguyen, & Olson, 2015, see Figure 4b). Our mixed methods study (Yim, Wang, Olson, Vu, & Warschauer, 2017) used DocuViz to identify the distinct patterns and characteristics of undergraduate groups’ synchronous writing on Google Docs and their impacts on the quality and quantity of group texts. The visualization charts were qualitatively coded and categorized into four distinct patterns (see Figure 5): (a) main writer style dominated by one or two main writers, (b) divide and conquer style displaying parallel and simultaneous composition of individual sections in real-time, (c) cooperative revision style involving peer feedback at the later stages of the composition process, and (d) synchronous hands-on style in which members build off each other's texts during a “simultaneous branching of ideas,” as described by an interviewee.…”
Section: Text Mining and Visualizationsmentioning
confidence: 99%
“…We further extended this line of inquiry by looking more specifically at the role of contextual factors that shape collaboration in a middle school context (Yim & Warschauer, 2019a). In a longitudinal case study that followed 102 students’ yearlong synchronous collaborative writing practices in a middle school with a large population of language minority learners, we examined multiple aspects of collaborative writing characteristics (i.e., balance of written participation, editing amount, the use of collaborative writing strategies) using DocuViz.…”
Section: Text Mining and Visualizationsmentioning
confidence: 99%